Determinasi Produktivitas Karyawan pada Perusahaan Transportasi: Analisis Kompetensi, Motivasi dan Efikasi Diri dimediasi Remunerasi - Sonya Sidjabat; Kamsariaty Kamsariaty; Josua Panatap Soehaditama; Mochammad Subagio; Abi Prasidi (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to develop hypotheses related to factors that influence employee productivity mediated by remuneration, especially in the transportation sector. The approach used in this literature review study is descriptive qualitative. The data collection technique is to use literature studies or review previous relevant articles. The technique used in this literature review is Comparative Analysis. The data used in this descriptive qualitative approach came from previous studies relevant to this study and sourced from academic online media such as Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Q2-Q4 Emerald, Elsevier, Sage, Web of Science, Sinta 2-5 Journal, DOAJ, EBSCO, Google Scholar, Copernicus, and digital reference books. The results of this literature review are: 1) Competence affects remuneration; 2) Motivation affects remuneration; 3) Self-efficacy affects remuneration; 4) Competence affects employee productivity; 5) Motivation affects employee productivity; 6) Self-efficacy affects employee productivity; 7) Remuneration affects employee productivity; 8) Competence affects employee productivity through remuneration; 9) Motivation affects employee productivity through remuneration; 10) Self-efficacy affects employee productivity through remuneration.